2021
DOI: 10.20944/preprints202103.0583.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantum Computing Aided Machine Learning Through Quantum State Fidelity

Abstract: Tremendous progress has been witnessed in artificial intelligence within the domain of neural network backed deep learning systems and its applications. As we approach the post Moore’s Law era, the limit of semiconductor fabrication technology along with a rapid increase in data generation rates have lead to an impending growing challenge of tackling newer and more modern machine learning problems. In parallel, quantum computing has exhibited rapid development in recent years. Due to the potential of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Experiments were conducted on quantum stimulators, and the performance of IonQ and IBM-Q quantum platforms was determined by accessing Microsoft's Azure Quantum platform. From the results, it was shown that Quclassi performed better than Tensorflow quantum, quantum-based solutions, and quantum flow for multi-class and binary classification [16]. QuClassi showed better performance in comparison with the conventional DNN and attained 97.37% accuracy with fewer parameters.…”
Section: Review Of Existing Workmentioning
confidence: 97%
“…Experiments were conducted on quantum stimulators, and the performance of IonQ and IBM-Q quantum platforms was determined by accessing Microsoft's Azure Quantum platform. From the results, it was shown that Quclassi performed better than Tensorflow quantum, quantum-based solutions, and quantum flow for multi-class and binary classification [16]. QuClassi showed better performance in comparison with the conventional DNN and attained 97.37% accuracy with fewer parameters.…”
Section: Review Of Existing Workmentioning
confidence: 97%
“…The past decade has witnessed the great successes of machine learning in many areas [1]. However, with the end of Moore's law and the rapidly increasing demands for machine learning, it is necessary to develop new computing machines [2][3][4]. Quantum computing is a potential candidate that has exceeded modern supercomputers in the specific tasks of random circuit sampling and boson sampling [5,6].…”
Section: Introductionmentioning
confidence: 99%